Analysis of internal processes of conflict behavior among Iranian rangeland exploiters: Application of environmental psychology - Haji, Latif; Hayati, Dariush (Frontiers in Psychology, 2022)
Conflicts over rangeland exploitation have been a serious challenge in Iran, rooted in human behavior. Accordingly, this study aimed to provide a comprehensive theoretical framework in the field of analyzing conflict behavior among rangeland exploiters. This research is a descriptive-correlational and causal-relational study conducted using a cross-sectional survey. The statistical population of the study was rangelands exploiters in one of the northwest provinces of Iran (N = 66867) of whom 384 people were selected as a sample and stratified random sampling method with proportional assignment. The research instrument was a questionnaire the validity of which was confirmed by a panel of academic experts and the reliability of its items was verified using Cronbach’s alpha coefficient. The results showed that the variables of personal norms and the perceived behavioral control were able to predict 25.9 percent of the variance in terms of the conflicting behavior of rangeland exploiters; besides, ascription of responsibility, personal norms, perceived behavioral control, and awareness of consequences, which have been proposed as activators of personal norms, were able to explain a significant percentage (63.5 percent) of the variance in terms of personal norms. Furthermore, analysis of the effects of environmental and cultural values showed that conflict behaviors of exploiters were mostly affected by their underlying values. Generally, the results of this study would help in the development of more integrated and comprehensive models in the field of exploiters' conflict behavior. Eventually, to change and improve the environmental behavior of exploiters to better management of conflict in rangelands, providing a list of considerations and competencies for agricultural extension and education, this article comes to the end.